2004
DOI: 10.1093/hmg/ddh168
|View full text |Cite
|
Sign up to set email alerts
|

Variation in USF1 shows haplotype effects, gene : gene and gene : environment associations with glucose and lipid parameters in the European Atherosclerosis Research Study II

Abstract: Upstream stimulatory factor 1 (USF 1), is a transcription factor controlling expression of several genes involved in lipid and glucose homeostasis and co-localizes with familial combined hyperlipidemia (FCHL) and type 2 diabetes on chromosome 1q22-23. We sequenced USF1 in 24 UK FCHL probands, but found no rare or common cSNPs. Three common intronic single nucleotide ploymorphisms (SNP), 306A>G, 475C>T and 1748C>T, were identified and their association was examined with fasting and postprandial lipids and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
4

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 48 publications
8
73
4
Order By: Relevance
“…No significant associations between various USF1 polymorphisms or haplotypes, inferred from these SNPs and TC and HDL cholesterol concentrations, were found in our study, which again is in agreement with most published studies so far (18,24,26,27,29). In Dutch FCHL families, genetic variants within the USF1 gene were associated with TC (18,44).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant associations between various USF1 polymorphisms or haplotypes, inferred from these SNPs and TC and HDL cholesterol concentrations, were found in our study, which again is in agreement with most published studies so far (18,24,26,27,29). In Dutch FCHL families, genetic variants within the USF1 gene were associated with TC (18,44).…”
Section: Discussionsupporting
confidence: 92%
“…In a Swedish male cohort, the minor allele of rs2073658 highly correlated with rs3737787 was associated with higher LDL cholesterol levels (28). By contrast, a population-based Korean study and the EARSII study found no association between LDL cholesterol and genetic variants within the USF1 gene, but there was indication of interaction between genetic variants in the USF1 gene and fasting LDL cholesterol (27,29).…”
Section: Discussionmentioning
confidence: 91%
“…In 800 young men from the European Atherosclerosis Research Study, Putt et al (26) tested three intronic USF1 SNPs (one of which, rs2073655, was in complete LD with the SNPs displaying the strongest FCHL association signal in Finns) reporting weak haplotypic associations with glucose levels during an oral glucose tolerance test. A recent study in Hong Kong Chinese reported associations of USF1 SNPs (including rs3737787) with type 2 diabetes and metabolic syndrome in one case-control analysis (using family cases showing 1q linkage), but these were not replicated in a second Chinese sample (27).…”
mentioning
confidence: 99%
“…Metabolic syndrome, type 2 diabetes and FCHL have all been linked to the USF1 gene [35][36][37]. A number of risk alleles of USF1 have been identified, which all represent variants of the non-coding sequence [36,38,41]. It is not clear how non-coding polymorphisms in USF1 may contribute to these metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how they convey glucose or insulin responsiveness to susceptible target genes. In USF1 a number of polymorphisms have been reported [36,38,40], some of which are associated with unfavourable results in oral glucose and fat tolerance tests [41], increased adipocyte lipolysis [42] and decreased expression of USF target genes in fat biopsies [40]. In nonhepatic cells, glucose has been shown to increase nuclear expression of either USF1 or USF2 [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%